MORPHOLOGICAL AND PHYSICAL PROPERTIES OF ZnO NANOSTRUCTURES GROWN ON Sb-DOPED ZnO SEEDING FILMS ANNEALED UNDER DIFFERENT ATMOSPHERES - Wuttichai Sinornate; Hidenori Mimura; Wisanu Pecharapa (Surface Review and Letters, 2021)
In this work, morphological and physical properties of pyramid-like ZnO nanostructures fabricated on Sb-doped ZnO seeding films annealed under different atmospheres are extensively studied. The Sb-doped ZnO seeding films were first prepared by sol–gel spin coating technique onto glass substrate then annealed in nitrogen, air and argon followed by low-temperature hydrothermal process for ZnO nanostructures fabrication. The morphological results exhibit the growth of pyramid-like ZnO nanostructure with increasing density of the ZnO nanostructures. The crystal structure shows pyramid-like ZnO wurtzite hexagonal growth along the c-axis without any impurity phase. The growth of pyramid-like ZnO nanostructures is due to the high growth rate of (002) plane. Photoluminescence spectra exhibit the near-band-edge of all samples while the red emission appears in ZnO nanostructures after the hydrothermal process due to the imperfection in the crystal. The reflectance of ZnO nanostructures covers the visible region with the absorption edge of 375[Formula: see text]nm. The calculation shows the relevant energy band gaps in the range of 3.26–3.28[Formula: see text]eV. The difference in hydrothermally grown ZnO nanostructures is significantly affected by different annealing atmospheres.
Keywords: ZnO doping and properties; Ga2O3 and related materials; Gas Sensing Nanomaterials and Sensors